2017
DOI: 10.3389/fpsyt.2017.00033
|View full text |Cite
|
Sign up to set email alerts
|

Early Psychosis and Trauma-Related Disorders: Clinical Practice Guidelines and Future Directions

Abstract: Despite high rates of trauma-related disorders among individuals with early psychosis, no clinical practice guidelines for the treatment of comorbid early psychosis and trauma-related disorders exist to date. Indeed, the routine exclusion of individuals with past and current psychosis from participation in trauma research and practice has limited the accumulation of research that could support such clinical practice guidelines. While preliminary research evidence suggests that traditional, evidence-based treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Our results here also specifically highlight the need to screen for all forms of trauma, not only abuse and neglect. Unfortunately, there are a lack of evidence-based interventions for trauma in the CHR syndrome with only recent attention to PTSD treatment in schizophrenia, and many clinicians express discomfort with addressing trauma in psychotic-spectrum conditions (Cragin et al, 2017;Gairns et al, 2015). Thus, our current treatment recommendations are limited to individual adaptations of trauma-informed and trauma-focused treatments (Swan et al, 2017), pointing to a substantial clinical need and direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Our results here also specifically highlight the need to screen for all forms of trauma, not only abuse and neglect. Unfortunately, there are a lack of evidence-based interventions for trauma in the CHR syndrome with only recent attention to PTSD treatment in schizophrenia, and many clinicians express discomfort with addressing trauma in psychotic-spectrum conditions (Cragin et al, 2017;Gairns et al, 2015). Thus, our current treatment recommendations are limited to individual adaptations of trauma-informed and trauma-focused treatments (Swan et al, 2017), pointing to a substantial clinical need and direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the positive effects found in the psychoeducation group were not as large (effect sizes) and substantive as those in the FMSG. While psychoeducation group programs for families of people with schizophrenia and psychotic disorders are widely accepted and implemented in Western countries (810) and China (52), recent systematic reviews on family interventions (8–11) concluded that this approach can produce moderate but inconsistent benefits in families' burden, stress and illness management and well-being, especially in a longer term (>18 months) of follow-up. The findings of this study support a conclusion that family psychoeducation groups may be less likely to demonstrate sustainable benefits on family functioning at ≥12 months follow-up, as well as lower effects on different aspects of family and patient outcomes over 48 months post-intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the consistent and substantive symptom reduction (PANSS scores) and lower number of re-hospitalizations among the patients in the FMSG over the 4 years of follow-up may suggest much better illness/symptom management than those in both the TAU and psychoeducation group. While there have been increasing amounts of case controlled and prospective evaluation studies favoring the use of mutual support groups for patients with severe mental illness and their families, only few randomized controlled trials have been conducted to evaluate its effects or cost-benefits in community mental healthcare services (810, 15). In addition, the FMSG also demonstrated a stable or slightly reduced demand for community mental health services for patients and/or families and thus this approach might not result in any additional service needs or costs in the community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations